Development of Artificial Intelligence (AI): A Bibliometric Analysis Approach - Abdul Latif; Erna Apriani; Muhamad Syahwildan; Pupung Purnamasari (SEAN Institute, 2023)
The whole world is competing to develop artificial intelligence for the benefit of groups and individuals, and this condition results in significant changes in the style or way of human activity; the development of artificial intelligence in the world of technology is very rapid and inevitable. This research aims to systematically analyze the development of artificial intelligence in human technological civilization within the last three years, namely from 2010 to 2022. This research uses a bibliometric analysis approach assisted by the VOSviewer application. The data used is scientific article data published on Google Scholar during 2010-2022 using the Publish or Perish application on the keyword